Are R&D subsidies effective? The effect of industry competition - Xin Xiang (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
In this study, the author explores the effect of industry competition on public R&D subsidy effectiveness. He finds a non-linear threshold effect of industry competition on R&D subsidy effectiveness. Specifically, R&D subsidy effectiveness reaches its peak when industry competition lies between two estimated thresholds.
http://dx.doi.org/10.7910/DVN/30QTRI
Keywords: H25; L11; G31; G38; 330; industry competition; R&D subsidy; complement effect; threshold regression